Moralność krańcowa jako przedmiot badania oraz jako wiedza o sposobach osiągania przewagi konkurencyjnej - Rotengruber, Przemysław (Annales. Etyka w Życiu Gospodarczym, 2013)
The aim of this article is to scrutinise the relationship between the moral attitude of an entrepreneur and their possibility to gain a competitive advantage. This declaration leads to the following question: Whether the everyday practice confirms or denies the economic usefulness ofthe postulate of corporate social responsibility. On the one hand, moral desertion is obviously profitable (also in an economic sense). Partners of the deserter, in most cases, are not able to avoid (unexpected and expansive) the consequences of this new attitude towards them. On the other hand, this strategy – in the long run – is unlikely to be profitable. The former victims adjust to their new circumstances and become ready to face the attack. Therefore corporate social responsibility, in the final calculation, should be taken as the only way to protect an active participant of the market against the temptation to neglect his obligation towards people, who can punish or reward him (as stakeholders or whistleblowers).